Changes in foot volume, body composition, and hydration status in male and female 24-hour ultra-mountain bikers - Chlíbková, Daniela (BioMed Central, 2014)
The effects of running and cycling on changes in hydration status and body composition during a 24-hour race have been described previously, but data for 24-hour ultra-mountain bikers are missing. The present study investigated changes in foot volume, body composition, and hydration status in male and female 24-hour ultra-mountain bikers.

The effects of running and cycling on changes in hydration status and body composition during a 24-hour race have been described previously, but data for 24-hour ultra-mountain bikers are missing. The present study investigated changes in foot volume, body composition, and hydration status in male and female 24-hour ultra-mountain bikers.
Changes in foot volume, body composition, and hydration status in male and female 24-hour ultra-mountain bikers
Keywords: Body mass; Fat mass; Hydration; Foot volume; Body mass; Fat mass; Hydration; Foot volume